(3agGQS cJGH GdCZGfjs - (3YHO GddWja Hf YHO GdQMef Hf ESeGYjd, ef Bd KfjGf,J (B1363 (3g` s ((3HNW GdeDda (B((3UGfY GdagQS(B) s)
(3ChdgG (B:s
(3CeG HYO Gfj hEf cfJ eef TZdg GdReGf HGdEcJSGH abO UGQ dj hdY aj eWGdYg cJH GdCOH s
(3BNQgG (B:s
(3Je hddg GdMeO agQS bhGaj GdTYQ hGdQLR GdJj GMJhGgG cJGH GdCZGfj ddYdGeI GHj aQL GdCUagGfj Ydi jO eSJNQLg s
(3HWHYI HhdGbs
(3hJJVef NeSI cTGaGJ(B: (3GjGe GdYQH hGdCYdGes
(3GdTYQGA hGdCecfIs
(3hGdbhGajs
(3ocJH dNRGfI GdCHGA GdcQedjf aj HZOGO s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs